Purification of Gastric Mucosal ECL Cells from a Crude Elutriation Fraction - John Graham (The Scientific World Journal)
Acid-secreting parietal cells from the gastric mucosa are widely studied as a model in studies on ion transport and the endocrine/paracrine ECL cells effectively control parietal cell function. Discontinuous gradients of iodixanol for the purification of ECL cells were subsequently simplified to the use of a density barrier. This technique is now commonly used following initial centrifugal elutriation.